Outbreak of malignant catarrhal fever in cattle in Turkey - Dabak, M; Bulut, H (British Veterinary Assoc, 2003)
[Abstract Not Available]
Keywords: Linked-Immunosorbent-Assay; Republic-of-Ireland; Sheep; Diagnosis; Pcr